OVIPOSITION BEHAVIOUR OF A RICE FIELD CHIRONOMID, CHIRONOMUS SAMOENSIS_EDWARDS (DIPTERA : CHIRONOMIDAE) - CHATTOPADHYAY, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Oviposition behaviour of the common rice field breeding chironomid, Chironomus samcensis_Edwards was studied in laboratory condition and it was noticed that females of this species preferred floating objects for oviposition. The time of oviposition was limited in the evening hours only.